Spinal Tuberculosis: Comparative Study Between Surgical & Conservative Management - Rashid, Mohammad Humayun; Ahmed, Ansar Uddin; Sarker, Tapas; Ohi, Sirajul Munir (Bangladesh Journal of Neurosurgery, 2026)
Background: Due to globalization, spinal tuberculosis is no longer a disease limited to developing nations and accounts for 50%-60% of osseous TB. Worldwide conservative treatment including anti-tubercular therapy is popular but along with surgical treatment plays a vital role. Methods: This hospital-based comparative study was conducted in a multi-disciplinary hospital for two years. A total of 38 cases were enrolled into the study out of which 22 cases with spinal tuberculosis underwent surgical management and 16 cases were treated conservatively. All patients were treated with standard anti-TB drugs and the addition of add-on therapy by Levofloxacin as per National Antitubercular Therapy Guideline pre- and postoperatively where applicable and were followed regularly after 3 months. Neurological function and pain were evaluated in all cases during admission and post procedure where applicable by ASIA grade scale and visual analogue scale (VAS) respectively. Outcomes were finally assessed 3 months after initiation of treatment. Results: Out of 38 cases, 4 were lost to follow-up. Among the available 34 cases, 18 were men and 16 were women. The mean age was 37.10 (±14.70) years and age range was 18 to 56 years. At 3 months final follow-up, the VAS score significantly improved from 7.97 (±1.27) pre-procedure to 1.23 (±0.69) post procedure (P < 0.001) and all patients became pain less, with final VAS score 0-3. At the 3 months follow-up, the ESR and CRP significantly improved from preoperative status (P < 0.001). Thirty-one (91.76%) patients improved by at least one ASIA grade and the remaining three (8.82%) patient maintained their preoperative ASIA grade as before. Post-operative deterioration was observed in three cases who developed bed sore and its complications. Out of 13(38.23%) cases with bowel bladder dysfunction before surgery 9 (83.9%) recovered within three months. Conclusion: Surgical management has a satisfactory outcome but certain cases can be managed conservatively depending on several factors. Clinicians must judicially select cases for optimum outcomes. Bang. J Neurosurgery 2025; 14(2): 90-99